1992
DOI: 10.1002/jcp.1041520225
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate beads as a slow‐release system for delivering angiogenic molecules In Vivo and In Vitro

Abstract: A method previously used in this laboratory for entrapment of tumor cells in alginate beads has been extended to provide a slow release delivery system for growth factors with known in vivo angiogenic activity. Protein growth factors were entrapped in alginate beads in amounts sufficient to cause incorporation of 3H-thymidine by COMMA-D cells in vitro, and in vivo neovascularization when injected subcutaneously into Balb/c mice. Entrapment of 125I-labelled growth factors showed that the amount of molecule entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(63 citation statements)
references
References 35 publications
1
62
0
Order By: Relevance
“…This delivery system allows prolonged (4 to 6 weeks) sustained release (first-order kinetics). 8,10,23 In animal studies, there was a dose-dependent effect of bFGF that was not associated with detectable serum levels, hemodynamic effects, or local or systemic toxicity. 5,8 Of the 46 patients judged to have a major coronary artery that could not be grafted on the basis of angiographic appearance, 22 patients were actually successfully grafted at the time of CABG.…”
Section: Discussionmentioning
confidence: 99%
“…This delivery system allows prolonged (4 to 6 weeks) sustained release (first-order kinetics). 8,10,23 In animal studies, there was a dose-dependent effect of bFGF that was not associated with detectable serum levels, hemodynamic effects, or local or systemic toxicity. 5,8 Of the 46 patients judged to have a major coronary artery that could not be grafted on the basis of angiographic appearance, 22 patients were actually successfully grafted at the time of CABG.…”
Section: Discussionmentioning
confidence: 99%
“…The values of n for membranes prepared by using various amounts of PEO (10,20, and 30 wt.%) while keeping VHCl (15%) and GA (3 ml) constant, ranged from 0.487 to 0.712 leading to a shift of transport from Fickian to the anomalous type. The VHCl-loaded membranes exhibited n values ranging from 0.463 to 0.675 (see Table 2), indicating the shift from erosion type release to a swelling controlled, nonFickian type mechanism.…”
Section: Drug-release Kinetic Parameters Of Different Formulationsmentioning
confidence: 99%
“…Correlation coefficients, r, obtained while fitting the release data are in the range from of 0.934 to 0.997. Figure 6 shows the release profile of VHCl-loaded membranes SP-1, SP-2, and SP-3 at different amounts of drug loading (10,15, and 20 wt.%, respectively) in phosphate buffer solution pH 7.4 (PBS) at 37°C. The release data show that the membrane containing higher amount of VHCl drug (SP-3) displayed faster and higher release rates than those formulations containing lower amount of VHCl.…”
Section: Drug-release Kinetic Parameters Of Different Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous in vitro studies have identified a stabilizing effect of alginate beads on hydrophilic b-lactam antibiotics and epithelial proliferation growth factors. 8,18,[20][21][22][23][24][25] Thus, alginate is a potential vehicle in a biodegradable carrier system for both antibiotics and bone cells.…”
Section: Introductionmentioning
confidence: 99%